Guo yu Luoma zi ru men - Xiao, Dichen (Beiping : Guo yu Luoma zi cu jin hui, 1932)
Gong 8 zhang. Jiang shu zi mu, sheng diao deng.
Fu lu: Guo yu Luoma zi ju li.
Keywords: Chinese language -- Transliteration